Electrochemical Investigations on TiO2-B Nanowires as a Promising High Capacity Anode for Sodium-ion Batteries. (10th May 2016) - Lee, Jeongyeon; Lee, Joong Kee; Chung, Kyung Yoon; Jung, Hun-Gi; Kim, Haesik; Mun, Junyoung; Choi, Wonchang
Highlights: TiO2 -B nanowire exhibits high discharge capacity of 196 mAh g −1 . TiO2 -B nanowire presents long cycleability of 150 mAh g −1 at 50th cycle. 1 mole of TiO2 -B can uptake 1 mole of Na + during the initial charge. Only 60% of intercalated Na + in TiO2 -B can be deserted during the 1 st discharge. Good surface electrolyte interface successfully forms after the 1 st cycle. Abstract: We report the electrochemical behaviors of TiO2 -B nanowire electrodes exhibiting a high operating potential where they can avoid severe Na plating and a de-sodiation capacity of 196 mAh g −1, which is the highest among several types of titanium oxides reported for sodium ion batteries. When TiO2 -B nanowires are used as negative electrodes for sodium ion batteries, 1 mole of the TiO2 -B nanowire can take up approximately 1 mole of sodium ions during the sodiation process and reversibly relieve 0.6 mole of intercalated sodium during the subsequent de-sodiation process. It has been proved that TiO2 -B nanowire electrodes participate in a reversible single-phase Na insertion/desertion reaction during charge and discharge. The electrodes exhibit irreversible capacity, owing to electrolyte decomposition and residual irreversible Na insertion, as determined via in situ XRD, ICP, FE-SEM, XPS, and electrochemical analyses. Further, TiO2 -B is a superior material exhibiting long and stable cyclability with a specific capacity of 150 mAh g −1 over 50 cycles.